Extension from Core to No-Core Nuclear Shell Model with Hartree–Fock wave Function: Application to Positive-Parity States in 19F - Ghafoor, Berun N.; Fatah, Aziz H.; Ahmed, Ari K. (East European Journal of Physics, 2025)
This work presents a detailed investigation of low-lying positive-parity states in the 19F nucleus by combining shell-model techniques with Hartree–Fock (HF) calculations. The study systematically extends from traditional core-based spaces (sd, zbm, psd) to the fully untruncated no-core configuration (spsdp f). Realistic single-particle wavefunctions were generated using harmonic oscillator (HO), Woods–Saxon (WS), and Skyrme parameterizations. The approach was tested across a broad set of observables, including excitation spectra, electromagnetic form factors (C0, C2, C4, M1, M3, E2, E4, and E4+M5), transition probabilities, magnetic dipole and electric quadrupole moments, as well as binding energies and rms charge radii. Discrepancies reported in earlier theoretical work, particularly for the M1 and C4 transitions at higher momentum transfers, were resolved through expanded model spaces and refined radial wavefunctions. Together with our previous study of negative-parity states in 19F, these results provide a coherent picture: systematic core-to-no-core extensions are essential for accurately reproducing both detailed and bulk nuclear properties. This unified framework strengthens theoretical modeling of 19F and establishes a foundation for future shell-model studies of nuclei in transitional and deformed regions.